Robot-assisted vs. laparoscopic nephroureterectomy for upper urinary tract urothelial carcinoma: a systematic review and meta-analysis based on comparative studies - Ji, Ruoyu; He, Zhangyuting; Fang, Shiyuan; Yang, Wenjie; Wei, Mengchao; Dong, Jie; Xu, Weifeng; Ji, Zhigang (Frontiers in Oncology, 2022)
Background: Robot-assisted nephroureterectomy (RANU) and laparoscopic nephroureterectomy (LNU) are two minimally invasive surgical management for upper urinary tract urothelial carcinomas (UTUC). Though more high-tech, it remains largely unclear whether RANU provides additional benefits over LNU. We aimed to quantitatively compare the perioperative and oncologic outcomes between RANU and LNU. Methods: The systematic review was performed based on a registered protocol (registration number CRD42022319086). We searched through PubMed, EMBASE and Cochrane databases, as well as conference proceedings and references of review articles (May 2022) for comparative studies reporting perioperative and oncologic outcomes independently in RANU and LNU groups. Selection of studies and data extraction were performed independently by two researchers. Risk of bias was assessed using the modified Newcastle-Ottawa Scale. Results of random-effects meta-analyses were presented as mean differences (MD) or Odds ratio (OR), as appropriate. Subgroup and univariate meta-regression analyses were performed to identify interstudy heterogeneities. Results: The review included 8470 patients undergoing RANU and 19872 patients undergoing LNU from 12 comparative original studies. RANU was associated with fewer overall complications (OR=0.71, 95%CI: 0.62 to 0.81), longer operative time (MD=27.70, 95%CI: 0.83 to 54.60) and shorter length of stay (MD=-0.53, 95%CI: -0.98 to -0.07) compared to LNU. In addition, patients receiving RANU were more likely to have lymph node dissected (OR=2.61, 95%CI: 1.86 to 3.65). Recurrence and survival outcomes did not differ between two surgical procedures. Sample size, types of LNU and world region were major sources of heterogeneity. Conclusion: For UTUC patients, RANU offers fewer complications and shorter hospitalization. However, RANU requires longer operative time and shares similar oncologic outcomes compared to LNU. Further randomized designed studies are warranted.